Effect of titanium in-situ alloying on the microstructure and mechanical properties of the RHEAs MoNbTaW system - Bernardo. L. Ribeiro; Peter Grün; Filofteia-Laura Toma; Leonid Gerdt; Joerg Kaspar; Maria Barbosa; Rúben F. Santos; Elsa W. Sequeiros (European Journal of Materials)
Refractory high-entropy refractory alloys (RHEAs) are emerging as potential alternatives to Ni-based superalloys due to their exceptional high-temperature properties. Among them, the MoNbTaW system shows promising characteristics, though brittleness at room temperature limits practical use. In the present study, the titanium (Ti) in-situ alloying through Laser Direct Energy Deposition (L-DED), combined with thermodynamical calculations for phase prediction, presented as a high-throughput screening methodology to gather immense new information on RHEAs based on the MoNbTaWTi system. Thermodynamic calculations showcase that the addition of Ti, up to 50 at. %, allow a single-phase BCC structure. Experimentally, it was observed that most Ti additions lead to sustaining the BCC structure; however, due to Ti’s lower melting point, some interdendritic heterogeneity was observed. EBSD analysis shows that the alloying with Ti can lead to an exchange in predominant crystallographic orientation while presenting no significant effect on the grain size. Microhardness tests show that the highest hardness increase is obtained for ∼24 at% of Ti, linked to a solid solution strengthening. Based on these results, it was possible to qualify L-DED as a RHEAs screening technology and expand the practical knowledge of these alloys, thus accelerating their potential application in aerospace applications.